Formulation of Emulsified Modification Bitumen from Industrial Wastes - Mohd Najib Razali; Syarifah Nur Ezatie Mohd Isa; Noor Adilah Md Salehan; Musfafikri Musa; Mohd Aizudin Abd Aziz; Abdurahman Hamid Nour; Rosli Mohd Yunus (Universitas Gadjah Mada, 2020)
The aim of this research was to characterize and analyze the formulation of emulsified modification bitumen (EMB) as well as the industrial wastes used in the formulation. Bitumen being a non-renewable product with severe environmental issues arising lately led to the use of industrial wastes such as plastic and recycled base oil in this research. Physical characteristic studies were performed to analyze the decomposition temperature, boiling point, flash point, density, moisture content, element content in waste plastics, and flowability of bitumen emulsion. Eight ratios of modified bitumen were formulated and compared with the industrial grade bitumen. The modified bitumen with a penetration value of 103 mm and softening value at 49 °C was chosen for the emulsification process where three emulsifiers were added into the mixture of bitumen and water. These samples were compared with the industrial bitumen emulsion. From the analysis, the formulated emulsion was obtained from a mixture consists of 20% bitumen, 7% polymer, and 73% recycled base oil.